Factors that influence parental satisfaction with SDF treatment in healthy children and those with special healthcare needs - Crystal, Y. O.; Jang, J. H.; Janal, M. N.; Raveis, V. H. (Frontiers in Dental Medicine, 2023)
Purpose: Silver diamine fluoride (SDF) is used as a caries management agent for the arrest of dentinal caries lesions. The purpose of this study was to evaluate the satisfaction with SDF treatment provided at a university pediatric dentistry clinic, and to identify factors that may contribute to parental dissatisfaction. Methods: We obtained retrospective data of children who received SDF treatment at our clinic from February 1st, 2019 to February 28th, 2021. Parents were contacted by phone to participate in a survey that evaluated their satisfaction with the treatment. Satisfaction was evaluated as a function of medical status, ease of treatment, outcome of SDF treatment, esthetics, and understanding of the treatment’s goals and side effects using contingency tables and chi-square statistics. Results: From 209 children who received SDF treatment, we were able to contact 91 parents by telephone, and 79 agreed to participate. Special healthcare needs (SHCN) patients were over represented in our sample, comprising 22.3% of all treated and 36.7% of participants. More than 90% were satisfied with the treatment, would do it again and would recommend it to others. Among the 49 children who complained of pain, SDF treatment resolved 82% of these complaints. In the subsample with follow-up in our clinic, approximately half of the treated teeth later received restorative treatment or were extracted, and the other half presented without further treatment. Some children received further treatment elsewhere. Parental dissatisfaction was related to staining of the anterior teeth (p= 0.04), the need for further treatment (p= 0.02) and a lesser understanding of side effects (p= 0.002). Conclusion: Most parents were satisfied with SDF therapy as a dental treatment choice due to its easy application and desensitizing effects. Our findings indicate that parental understanding of the interim nature of the treatment and staining of the lesions are important to achieve parental satisfaction.